New York Bank Clearings and Stock Prices, 1866-1914 - Matthews, Ada M. (The Review of Economics and Statistics, 1926)
IN IIg an analysis of New York bank clearings and railroad and industrial stock prices for the period I903-I4 showed that these three speculative series displayed similar cyclical fluctuations, preceding corresponding fluctuations of outside bank clearings and money rates by several months.2 With the object of testing the synchronism of the cyclical fluctuations of the speculative series for a longer period of years, the study has been extended back to i866; and comparisons of the series for the entire period I866-I9I4 are set forth in this paper. For the period 1903-I4 the data underlying these comparisons were taken from the previous study. For the period I866-I902 new data were assembled. Monthly items for bank clearings for I866I902 were obtained from the Commercial and Financial Chronicle.3 In order to obtain a continuous series of monthly railroad stock prices beginning with I866, it was necessary to join three indexes. For the period I866-80 there was available the index of the prices of Io railroad common stocks previously published in this REVIEW.4 For the years I88I-96 no index was available and a new monthly index of the prices of Io railroad common stocks was constructed. This index is described in detail in the Appendix to this paper, pp. I93-98. For the remainder of the period under examination, we used the Dow-Jones index of railroad stocks, available from I897.5 These three indexes, which are on different bases, were adjusted to form a continuous series on the level of the Dow-Jones index by the use of factors based on overlapping data. Indexes of industrial stock prices were available in monthly form beginning with I872. For the years I872-96 the series compiled by the New York Federal Reserve Bank was available, and from I897, the Dow-Jones index.6 As the series for I872-96 was obtained by working backward from the Dow-Jones list of I2 stocks in I897, adjustment of the series for the two periods was unnecessary. No indexes of industrial stock prices were available earlier than I872 because of the lack of representative organized markets. Similarity in the cyclical fluctuations of the three speculative series would probably have been revealed by plotting them on the same logarithmic chart. But comparison would have been difficult at times owing to the diverging or crossing of the curves the result of varying trends. In New York bank clearings the general movement was upward throughout the period (Chart 2). A moderate, steady rate of growth persisted from i866 to I896, followed by a sharper upward trend during a transitional period which lasted until I903. Thereafter until the end of the period, the rate of increase was less marked. The series for railroad stock prices was subject to both changes in the character of the long-time movement and pronounced shifts of level. During the years i866 to about I882 the trend was uncertain; the succeeding movement, not far from horizontal, persisted until I897, and was followed by an abrupt transition in I897I903 to a markedly higher level, which was maintained through I9I4 (Chart 3). Industrial stock prices showed one sharp